(3GdRHO GdcGajI GdTGajI aj EHQGR ecfhfGJ ahGFO GdbGajIs - (3CHh GdHbGA eMeO GdCMeOj GdTGaYjs
(3ChdgG (B:s
(3hHYO aEf Ydhe GdCOH afhf eMceI HdjZI HOjYg eHQbYI HLeGd GdceGd ZGdjI QajYI s
(3BNQgG (B:s
(3hjSCd YHOGddg PG GdNRQLi ef eWGdYg EJMGag efg HGdOYGA CNQgG hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3fSNI ecQQI ef GdejcQhajde Qbe (B54 (3YQhV hbhGais
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3YQhV (B141) s
Keywords: (3GdYQhV hGdbhGais